(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A sensation of mental tension and pressure is referred to as stress. The stress is a form of mental or emotional anguish. Excessive stress will leads to affect the health like increasing the heart strokes, heart attacks, ulcers, mental, psychological disorders, depression and anxiety. The good sleep quality will give a variety of benefits like improvised in mental and physical health, reduced daytime sleepiness, improvise in fitness, improvement in psychological functioning. The sleep is more important for the regeneration of the body and maintenance of energy levels. The people sleep quality and quantity can easily be affected by changes in their physical and social circumstances. This will help to identify the relationship between stress, sleep quality and physical symptoms. Through this study we can identify whether the stress affects the sleep quality and the poor sleep quality make the difference in body or physical symptoms. This study will have investigation and analysis only on early adulthood people, both male and female are included in this study. Limited samples have taken for this this study. The purpose of this study is to identify the stress level, sleep quality and physical symptoms among early adulthood people because the young adults are more addicted to the mobile phones so this will cause increase the stress level. If the people have more stress will affect the sleep quality. When the sleep quality has changed it will leads to changes in the human body.